Peran Penataan Produk dan Suasana Toko terhadap Minat Beli Konsumen di King Mart Department Store - Nurfadila Laudje; Zulfia K. Abdussamad; Srie Isnawaty Pakaya (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study was to determine the effect of product display on consumer purchase intention, the effect of store atmosphere on consumer purchase intention, and the simultaneous effect of product display and store atmosphere on consumer purchase intention at King Mart Department Store Tolangohula. This study employed a quantitative approach with an associative research type. The population consisted of consumers who had visited and made at least one purchase. The sample was determined using a purposive sampling technique with the Lemeshow formula, resulting in 100 respondents. Data analysis was conducted using SPSS (Statistical Product and Service Solutions) version 27. The results showed that product display had a positive and significant effect on consumer purchase intention, with a t-value of 2.524 greater than the t-table value of 1.984. Store atmosphere also had a positive and significant effect on consumer purchase intention, with a t-value of 5.347 greater than the t-table value of 1.984. Simultaneously, product display and store atmosphere had a positive and significant effect on consumer purchase intention, with an f-value of 113.927 greater than the f-table value of 3.09. The magnitude of the influence of both variables was 70.1%, while the remaining 29.9% was influenced by other factors outside this study.